2014
DOI: 10.1017/s0021223713000289
|View full text |Cite
|
Sign up to set email alerts
|

Persistent or Eroding Impunity? The Divergent Effects of Legal Challenges to Amnesty Laws for Past Human Rights Violations

Abstract: Transitional countries have struggled to overcome impunity for human rights violations committed by past authoritarian regimes. While some scholars have hailed the emergence of a ‘justice cascade’, a ‘justice revolution’, and an ‘age of accountability’, our research highlights the persistence of amnesty laws despite efforts to erode them. This article examines 63 amnesties for human rights violations committed by state agents that were enacted in 34 transitional countries from 1970 to 2011, and the 161 challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As academic literature has analysed, states continue granting amnesties and similar exemption measures, even in cases of international crimes. 105 There are several grounds underlying these domestic practices, including the need to move on from violent pasts, 106 prevent future atrocities, 107 and/or pave the transition to democratic regimes. 108 Nevertheless, there are important trends in state practice that suggest the increasing inadmissibility or limitation of amnesties in cases of serious violations in terms of: subject-matter, i.e., international crimes excluded; intended beneficiaries; and requirements.…”
Section: Domestic Practicesmentioning
confidence: 99%
“…As academic literature has analysed, states continue granting amnesties and similar exemption measures, even in cases of international crimes. 105 There are several grounds underlying these domestic practices, including the need to move on from violent pasts, 106 prevent future atrocities, 107 and/or pave the transition to democratic regimes. 108 Nevertheless, there are important trends in state practice that suggest the increasing inadmissibility or limitation of amnesties in cases of serious violations in terms of: subject-matter, i.e., international crimes excluded; intended beneficiaries; and requirements.…”
Section: Domestic Practicesmentioning
confidence: 99%
“…Today, states are conducting amnesty proceedings as a recurring practice. 20 Amnesty popularly perceived as a method to prevent perpetrators from assuming their responsibilities. It is often understood as a way of avoiding fairness and promoting impunity.…”
Section: Providing Amnesty To Perpetratorsmentioning
confidence: 99%
“…A large-n analysis of challenges to 63 amnesties for human rights violations committed by State agents enacted in 34 countries between 1974 and 2011 has shown that 'Outside the [South American] region, it is rare for past amnesties even for the most serious offences to be annulled, however, a small number have been limited in a few cases.' 122 Similarly, in reflecting on the 'persistence of amnesties', Jeffery has observed that 'It remains the case that most perpetrators of human rights violations granted amnesties in the past can rest secure in the knowledge that it is highly unlikely that they will ever face prosecution for their crimes.' 123 Consequently, in many parts of the world, the vast majority of past amnesties remain in effect and have not had their scope limited to exclude serious crimes.…”
Section: B Durabilitymentioning
confidence: 99%